Fixed Point and Acute Point Theorems for New Mappings in a Banach Space - Toshiharu Kawasaki (Journal of Mathematics)
In a Hilbert space, concepts of attractive point and acute point are studied by many researchers. Moreover, these concepts extended to Banach space. In this paper, we introduce a new class of mappings on Banach space corresponding to the class of all widely more generalized hybrid mappings on Hilbert space. Moreover, we introduce some extensions of acute point and prove some acute point theorems.